2019
DOI: 10.31219/osf.io/npqj7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personal Identity Development in Cultural Context: The Socialization of Master Narratives about the Gendered Life Course

Abstract: The present studies focused on the role and socialization of biographical master narratives – cultural narratives that prescribe the types and ordering of events that should occur in one’s personal life identity narrative – by focusing on adolescent and emerging adult gender identity development. We employed a combined explanatory and triangulation mixed methods design. Study 1a (n = 414) was a survey study examining the expected biographical master narrative events for men and women, and the content of mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The first is that redemption is not a master narrative. McLean and Syed (2015) pointed to the importance of ' air time' in determining master narratives -that is, those stories that are heard and told frequently are more likely to serve as master narratives (see also McLean, Fordham, Boggs, Byers, Haraldsson, Lowe, & Syed, 2019;McLean, Shucard, & Syed, 2017). If this proposition is true, then these results suggest that redemption is not a master narrative.…”
Section: Unsupported Hypothesesmentioning
confidence: 98%
“…The first is that redemption is not a master narrative. McLean and Syed (2015) pointed to the importance of ' air time' in determining master narratives -that is, those stories that are heard and told frequently are more likely to serve as master narratives (see also McLean, Fordham, Boggs, Byers, Haraldsson, Lowe, & Syed, 2019;McLean, Shucard, & Syed, 2017). If this proposition is true, then these results suggest that redemption is not a master narrative.…”
Section: Unsupported Hypothesesmentioning
confidence: 98%
“…The first is that redemption is not a master narrative. McLean and Syed (2015) pointed to the importance of ' air time' in determining master narratives -that is, those stories that are heard and told frequently are more likely to serve as master narratives (see also McLean, Fordham, Boggs, Byers, Haraldsson, Lowe, & Syed, 2019;McLean, Shucard, & Syed, 2017). If this proposition is true, then these results suggest that redemption is not a master narrative.…”
Section: Unsupported Hypothesesmentioning
confidence: 99%
“…The exposure to new cultural narratives also provided students with new perspectives on their home culture, which is a common finding in the literature (Adam et al, 2018; Braskamp et al, 2009; Meca et al, 2017). Previous research with non-exchange populations has shown that deviating from dominant cultural narratives facilitates the identification of master narratives and increased engagement in identity processes (McLean et al, 2018, 2020). Supporting these findings, exposure to the contrasting master narratives found in the host culture provided students with the opportunity to consider whether they wished to retain or change their pre-existing beliefs, values, and goals.…”
Section: Discussionmentioning
confidence: 99%